A reunião: ferramenta e ritual de governo. Relações pessoais e mundo do Estado num assentamento na Zona da Mata de Pernambuco (Antropolítica - Revista Contemporânea de Antropologia, 2016)
The observation of a local meeting in a settlement project of the Brazilian agrarian reform, dramatizing a domestic conflict between beneficiaries, offers a privileged opportunity to analyse meetings as both a political technology and a ritual of government, providing a formal frame for interactions between the bureaucratic world of the State and the world of interpersonal relationships. The official definition of the situation, framed in conformity with bureaucratic norms, collides with the practical arrangements of local interpersonal relations. The management of the relationship between these two worlds relies on the mediation of the field bureaucrat. In the context of indirect rule, meetings give ritual substance to the fiction of “community”, an essential element of “participatory” government.